Antioxidant activity and total phenol content of white wine Žilavka - Marković, Marijana; Martinović Bevanda , Anita; Talić, Stanislava (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2015)
It is already well known that wine consist of different compounds with strong antioxidant activity. Among them, most common ones are different phenol compounds generally separated in two major groups; flavonoids and nonflavonoids. In this paper we determined total phenol concentration and antioxidant activity of Herzegovinian white wines. Eighteen commercially available white wines made from autochthonous grape varietiesŽilavka (vintage 2011) were analyzed. Total phenol content was determined spectrophotometrically according to the Folin-Ciocalteu method using gallic acid as a standard. Two distinct methods were used to assess the antioxidant activity of tested wines: spectrophotometric monitoring of 2,2-diphenyl-1-picrylhydrazyl(DPPH·)free radical scavenging activity and Briggs-Rauscher (BR) oscillating reaction method. Total phenol concentration in wine samples varied from 249.3 ±SDmgL-1 to 801. ±SDmgL-1 expressed as mg of gallic acid equivalent per liter of wine, determined from a standard calibration curve. Similar antioxidant activity was obtained by both performed methods. The antioxidant capacity obtained by DPPH·method ranged from 28.8%±SD to 70.2%±SD. In some cases, the results obtained using both, DPPH·and BR methods, confirmed the fact that wines with higher total phenol content have stronger antioxidant activity.